Development of contextual-based mathematics teaching materials to facilitate students' mathematical problem-solving ability on systems of linear inequalities in two variables - Ulfania Julisa; Maimunah; Kartini (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2026)
This study was motivated by students’ low mathematical problem-solving ability, particularly in solving contextual problems related to systems of linear inequalities in two variables. Students often experience difficulties in understanding problems, constructing mathematical models, drawing graphs, and determining the solution region because learning materials tend to emphasize procedural exercises rather than systematic problem-solving stages. This study aims to develop contextual-based mathematics teaching materials on systems of linear inequalities in two variables to facilitate Phase E students’ mathematical problem-solving ability. This research employed a Research and Development (R&D) design using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The developed product was validated by three mathematics education experts and tested through one-to-one evaluation, a small group trial involving six students, and a field test involving 35 students. The instruments used were validation sheets and student response questionnaires. The validation results showed an average score of 95.27%, categorized as very valid. The practicality test obtained an average score of 89.16% in the small group trial and 92.96% in the field test, both categorized as very practical. These findings indicate that the contextual-based mathematics teaching materials are valid and practical for use in learning systems of linear inequalities in two variables and can serve as an alternative teaching material to facilitate students’ mathematical problem-solving ability.